小学校体育授業における運動強度の種目特性：単元で取り上げる種目間の違いに着目して - 大坪, 健太; 小栗, 和雄; 鈴木, 康介; 春日, 晃章; 林, 陵平; 関谷, 竜成 (発育発達研究, 2019)
This study aimed to clarify the unit characteristics of physical exercise intensity in elementary school physical education classes. The subjects were 28 elementary school children (16 boys and 12 girls) in 5th grade. We carried out measurements of all six units of long jump, expression, tag rugby, hurdle run, tee ball, and athletic practice exercise held in physical education classes. For the measurement of exercise intensity, Lifecorder GS manufactured by SUZUKEN Co., Ltd. was used. To clarify individual differences in each unit, the coefficient of variation was calculated. To clarify the differences between units, we adopted a one-factor analysis of responses, and when a significant main effect was observed, multiple comparison tests were applied. When significant difference was observed, residual analysis was conducted to examine the influence of the proportion of the scene of which unit is large.As a result, the magnitude of individual differences in exercise intensity in each unit was different. In addition, exercise intensity in the hurdle run was significantly higher (p < 0.05) than in the other five units, due to the difference in unit exercise intensity. Exercise intensity in athletic practice exercise was significantly lower than that of other units (p < 0.05). Also, the difference in proportion of the four scenes by unit was recognized. Because the content of learning differs depending on the unit, and although the difference in physical activity intensity itself is not a problem, for classes in which physical activity intensity is extremely low, efforts to intentionally promote the physical activity of the children are suggested.